TWO PERSONAL LIBRARIES – ONE VISION: SIMONAS DAUKANTAS AND JURGIS PLATERIS - BONČKUTĖ, ROMA (Knygotyra, 2015)
The attempts of this article to delineate the origins of the modern perceptions of the Lithuanian culture and literacy are based on the consideration of Daukantas’ library catalogue Te tytuły ksiąg w tym Rejestrze spisanych znajdujące bez krzyżykow są darowane Panom Dowkontom Mitkajckim Pana Andrzeja Dowkonta synom w roku 1852 gim przemnie Szymona Dowkonta and Domas Kaunas monograph Bibliotheca Georgii Comitis de Plater. Simonas Daukantas and Jurgis Plateris are the first intellectuals, whose works contain ideas, heavily influenced by the culture of the Eastern Prussia. Although Daukantas and Plateris were Catholics, they were highly influenced by the history of Eastern Prussia and the Lithuanian writings of Lutherans. While studying in Vilnius University, Daukantas and Plateris were students of prof. Ignacanas Onasevičius who encouraged his disciples to study not only the history of Lithuania but also the history of Eastern Prussia. Thanks to his influence, Daukantas and Platerys were more inclined towards the works of Lietuvininkai – Lutheran Lithuanians living in Prussia – unlike other intellectuals of the Great Lithuania. Having been familiarized with the culture and history of Eastern Prussia, they were more predisposed to the diction of Lutheran writings; their example inspired them to advance the written language of the Great Lithuania. Daukantas and Plateris agreed that both the Prussian and Latvian writings were significant for the development of the written Lithuanian language because of their close relation to it. Both of these men accumulated books not only about the Lithuanian but also about Prussian and Latvian languages. They concurred that the intellectuals of the Great Lithuania had to be united and an institute must be established, where books of appropriate content would be published and where people would be educated in the Lithuanian language.
Keywords: ...